Analysis of frozen section in correlation with surgical pathology diagnosis - Tangde, Ashwini; Shrivastava, Vaidik; Joshi, Anil (International Journal of Research in Medical Sciences, 2019)
Background: Frozen section (FS) is a rapid diagnostic procedure performed on tissues obtained intraoperatively. This method serves useful purposes, such as determining the malignancy or benignancy of a suspected lesion, determining the adequacy of a biopsy of a suspected lesion, confirming the presence or absence of metastasis, and identifying small structures. But it bears many disadvantages and limitations, the most of which is the danger of incorrect diagnosis. Therefore, it is critical to determine efficiency of frozen section performance periodically. This study was performed to determine accuracy of frozen section by correlating the intra-operative frozen section diagnosis with final diagnosis on permanent sections. Methods: In this retrospective study, authors compared the results of frozen section with their final permanent section diagnosis in Government Medical College and Hospital, Aurangabad, Maharashtra, India during January 2017 to December 2018. Results: Study comprises 83 patients, of which 73 were female and 10 were male. Out of 83 cases, the diagnosis of 76 cases was concordant with conventional histopathology diagnosis while seven were discordant. This gave overall accuracy rate of 91.57% and discordant rate of 8.43%. The overall sensitivity was 85.71% and specificity was 97.92%. The positive predictive and negative predictive value was 96.77% and 90.38% respectively. Conclusions: The accuracy, sensitivity, specificity of frozen section diagnosis in this study are comparable with most international quality control statistics for frozen sections. The results suggest that the correlation of intra-operative frozen section diagnosis with the final histopathological diagnosis on permanent sections forms an integral part of quality assurance activities in the surgical pathology laboratory and specific measures should be taken to reduce the number of discrepancies.